Living-Donor Liver Transplant Using the Right Hepatic Lobe Without the - Akbulut, S; Yilmaz, M; Eris, C; Kutlu, R; Yilmaz, S (2013)
Although rare, major congenital defects of the hepatic veins are detectable at autopsy, advanced, noninvasive imaging techniques such as Doppler ultrasonography and multislice computed tomography can accurately define these anomalies. One of these anomalies is congenital absence of the main right hepatic vein. We present a 21-year-old woman living-liver donor candidate with congenital absence of the right hepatic vein who underwent an extended right donor hepatectomy. She was tested for transplant compatibility with her 45-year-old brother, who had chronic liver failure secondary to hepatitis B. Multislice computed tomography revealed an absence of the right hepatic vein, and the right hepatic lobe was drained by 4 inferior hepatic veins with diameters ranging from 4 to 8.4 mm. An extended right-donor hepatectomy was performed. A common-large opening drainage reconstruction model that included all of the inferior hepatic veins and middle hepatic vein was created using the saphenous vein and an aortic homograft. There were no postoperative complications related to hepatic venous drainage thanks to the common-large opening model. We demonstrate that a right donor hepatectomy is feasible in congenital absence of the right hepatic vein solving the drainage problem using common-large opening reconstruction technique. C1 [Akbulut, Sami; Yilmaz, Mehmet; Eris, Cengiz; Yilmaz, Sezai] Inonu Univ, Liver Transplant Inst, Fac Med, TR-44280 Malatya, Turkey. [Kutlu, Ramazan] Inonu Univ, Dept Radiol, Fac Med, TR-44280 Malatya, Turkey.